Credibility of Halal Logo Design among Consumers - Zuhudi, Nurul Wahidah Mahmud; Dolah, Jasni (School of Social Sciences, USM, 2017)
The credibility of halal logo certified by JAKIM must perform as a vital indicator in providing consumers with trustworthy components during product consumption. The recognition of halal logo will also be helping in raising potential brand awareness to avoid conflict and confusions to consumers. Previous research has indicated some point of view on the use of multiple patterns on crescent and moon applied for halal logo (Brill, Leiden, 1960), which is inconsistent to shows strong significance to consumers. The appropriateness aspect of putting correct symbols or shape for halal logo is particularly subjective, and yet has not been widely discussed. The objective of study is, i) to examine factors influencing consumers to recognize and perceive halal logo, and ii) to suggest appropriate visual recognition to enhance better understanding. Using self-administrative questionnaire as a method of gaining a result, this study has been conducted among consumers. The findings may reveal some recommendation in improving previous halal logo to grab a sense of required recognition and raise brand awareness, which significantly essential in spreading wider knowledge for halal industry.